Tanzanian Couples' Perspectives on Gender Equity, Relationship Power, and Intimate Partner Violence: Findings from the RESPECT Study. (24th December 2012) - Krishnan, Suneeta; Vohra, Divya; de Walque, Damien; Medlin, Carol; Nathan, Rose; Dow, William H.
Abstract : Intimate partner violence (IPV) is widely prevalent in Tanzania. Inequitable gender norms manifest in men's and women's attitudes about power and decision making in intimate relationships and are likely to play an important role in determining the prevalence of IPV. We used data from the RESPECT study, a randomized controlled trial that evaluated an intervention to prevent sexually transmitted infections in a cohort of young Tanzanian men and women, to examine the relationship between couples' attitudes about IPV, relationship power, and sexual decision making, concordance on these issues, and women's reports of IPV over 12 months. Women expressed less equitable attitudes than men at baseline. Over time, participants' attitudes tended to become more equitable and women's reports of IPV declined substantially. Multivariable logistic regression analyses suggested that inequitable attitudes and couple discordance were associated with higher risk of IPV. Our findings point to the need for a better understanding of the role that perceived or actual imbalances in relationship power have in heightening IPV risk. The decline in women's reports of IPV and the trend towards gender-equitable attitudes indicate that concerted efforts to reduce IPV and promote gender equity have the potential to make a positive difference in the relatively short term.